Pengaruh Massase Punggung terhadap Adaptasi Nyeri Persalinan Fase Aktif, Lama Kala II dan Perdarahan Persalinan pada Primigravida - Wiwin Renny Rahmawati; Siti Arifah; Anita Widiastuti (Jurnal Riset Kesehatan, 2015)
The study is to know the influence of massage towards the decrease of labour pain in active fase, lenght of stage II, and labour bleeding in primigravida at publich health center Magelang Selatan. Quasi-experimental design was applied with static group comparation, This design gave intervention, then measurement and observation was conducted. Experiment group got back massage then the second measurement and observation was conducted. This result of measurement was compared to control group. Ratio scale was used. Subject of this research was 40 person who agree to participate in this research. Data was analyzed using Man-Whitny u-test the findings there are the influence of back massage toward the decrease of pain labour in active fase, lenght of labour kala II and labour bleeding in primigravida with p Value 0,01, and Z value for primigravida -4, 112, the lenght of kala II labour -4, 023 and bleeding -3,949. This is really important that nurses and midwives can include massage in their interventions to primigravida mothers who have labour to minimize pain, shorthen kala II, and decrease labour bleeding.